Encouraging students’ active classroom partcipation through the use of participation rubrics and scoresheets. - Nadarajan, Shyamala (Universiti Sains Malaysia, 2014)
The teaching of English Language in Malaysian Polytechnic focuses on Communicative English. Many English lecturers are facing uphill task in encouraging the students to communicate and participate in classroom activities in order to implement the syllabus. The students are very awkward and shy towards the language and that leads the lecturers to explore ways to assist students to eliminate this problem.